Krytyka ekstensjonalizmu. O ogólności - Schmitz, François (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 1995)
In the paper author discusses ideas of L. Wittgenstein who renounced formalism which was characteristic of the "Tractatus" epoch. The change is connected with the adoption of a different conception of language which refers, among other, problems to the new approach to "generality" (e.g. to generalized sentences). Wittgenstein rejected the proposition of analytical reductionism which is a conviction that it is possible to reduce and analyse "generality". He changed his opinion connected with the theory of meaning. The problems discussed above, dealt with by earlier conceptions of Frege and Russell belong to important problems of the philosophy of logic and the philosophy of language.